Common Regulatory Pathways Mediate Activity of MicroRNAs Inducing Cardiomyocyte Proliferation - Torrini, Consuelo (Cell Rep, 2019)
Loss of functional cardiomyocytes is a major determinant of heart failure after myocardial infarction. Previous high throughput screening studies have identified a few microRNAs (miRNAs) that can induce cardiomyocyte proliferation and stimulate cardiac regeneration in mice. Here, we show that all of the most effective of these miRNAs activate nuclear localization of the master transcriptional cofactor Yes-associated protein (YAP) and induce expression of YAP-responsive genes. In particular, miR-199a-3p directly targets two mRNAs coding for proteins impinging on the Hippo pathway, the upstream YAP inhibitory kinase TAOK1, and the E3 ubiquitin ligase β-TrCP, which leads to YAP degradation. Several of the pro-proliferative miRNAs (including miR-199a-3p) also inhibit filamentous actin depolymerization by targeting Cofilin2, a process that by itself activates YAP nuclear translocation. Thus, activation of YAP and modulation of the actin cytoskeleton are major components of the pro-proliferative action of miR-199a-3p and other miRNAs that induce cardiomyocyte proliferation.